Post-infectious irritable bowel syndrome (PI-IBS) after infection with Shiga-like toxin-producing Escherichia coli (STEC) O104:H4: A cohort study with prospective follow-up. Issue 1 (February 2016) - Andresen, Viola; Löwe, Bernd; Broicher, Wiebke; Riegel, Björn; Fraedrich, Katharina; von Wulffen, Moritz; Gappmayer, Kerrin; Wegscheider, Karl; Treszl, András; Rose, Matthias; Layer, Peter; Lohse, Ansgar W
Background: In May/June 2011, the new Shiga-like toxin-producing Escherichia coli (STEC) strain O104:H4 caused the severest outbreak ever recorded of hemorrhagic enterocolitis in 3842 patients in Germany. Objectives: As bacterial enterocolitis is an established risk factor of subsequent irritable bowel syndrome (IBS), we aimed to estimate prevalence and incidence of post-infectious (PI)-IBS after six and 12 months in a cohort of STEC O104:H4 patients and to prospectively identify associated somatic and psychometric risk factors. Methods: A total of 389 patients were studied prospectively at baseline and at six and 12 months after STEC infection using STEC disease-related questionnaires and validated instruments for IBS (Rome III) and psychological factors. Frequencies and logistic regression models using multiple imputations were applied to assess predictor variables. Results: Prevalence of IBS increased from 9.8% prior to STEC infection to 23.6% at six and 25.3% at 12 months after STEC infection. In patients without IBS symptoms prior to STEC infection, incidence of new IBS was 16.9%. Logistic regression models indicated higher somatization and anxiety scores as risk factors for, and mesalazine treatment during, STEC infection as the only significant protective factor against IBS. No other factor analyzed, including disease severity, showed an association. Conclusions: PI-IBS rates following this unusually severe STEC outbreak were similar to what has been observed after other infectious gastroenteritis outbreaks. Our findings suggest that mesalazine may have reduced the risk of subsequent PI-IBS. As altered mucosal immune activity is a pivotal pathogenic factor in PI-IBS, our observation of a potential protective effect of mesalazine might be explained by its known modulatory action on mucosal immunity, and may warrant further investigation.